On derivations associated with different algebraic structures in group algebras - Arutyunov, Andronick (Eurasian Mathematical Journal, 2018)
The paper is devoted to the comparison of derivation algebras arising in associative and Lie structures of group algebras. We shall prove that an algebra of derivations given by Lie-structure contains an algebra of associative derivations. We will give a description of Lie derivations in terms of the gruppoid associated with an inner action of the group.